Study of physical and dielectric properties of bio-waste-derived synthetic wollastonite - Hossain S.S.; Roy P.K. (My University, 2025)
The aim of this study is to fabricate synthetic wollastonite from chicken eggshells (CES) and rice husk ash (RHA) through an economical solid-state route. Wollastonite was formulated with a stoichiometric amount of calcined eggshells (~99% CaO) and heat-treated RHA (~93% SiO 2 ) as ingredients and calcined at 1000, 1100, 1150 and 1200°C for 120 min. The XRD spectrum revealed single-phase para-wollastonite (monoclinic, P21/a) after annealing at 1100°C and 1200°C with calcined powder contents comprising mainly a phase of pseudo-wollastonite (anorthic, C-1). For dielectric measurement, only the para- and pseudo-wollastonite pressed powder was sintered at 1100 and 1200°C for 240 min. The obtained results showed a stable, low dielectric constant (ε׳) of about 4.5 to 6, losses (tanδ) of about 0.0026 to 0.00361 and resistivity of around 6–9 × 10 8 (Ώ-cm) at 100 kHz. These are highly promising characteristics which suggest that waste-derived synthetic wollastonite may be useable as an ingredient in electrical porcelain applications. © 2018, © 2018 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group on behalf of The Korean Ceramic Society and The Ceramic Society of Japan.